2005
DOI: 10.1111/j.0105-1873.2005.0670h.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized dermatitis due to codeine. Cross‐sensitization among opium alkaloids

Abstract: Opium alkaloids can cause immunological reactions. Cross-sensitization among them must be considered in these situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…This made avoidance of the allergen in the workplace difficult, and, in a number of cases, workers had to leave their employment because of ongoing ACD. Many of the cases reported in the literature haved described cross‐reactions between different opioids within the same class . Our data show that, of 11 patients with ACD, six reacted to at least two substances.…”
Section: Discussionmentioning
confidence: 54%
“…This made avoidance of the allergen in the workplace difficult, and, in a number of cases, workers had to leave their employment because of ongoing ACD. Many of the cases reported in the literature haved described cross‐reactions between different opioids within the same class . Our data show that, of 11 patients with ACD, six reacted to at least two substances.…”
Section: Discussionmentioning
confidence: 54%
“…Previously, cross-reaction in patch tests has been reported between codeine, morphine and diacetylmorphine [9,10]. After contact allergy to buprenorphine had been confirmed, our patient 1 was treated with codeine only with no flare-ups of allergic contact dermatitis.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies have suggested that cutaneous allergic reactions to codeine can be induced by the non-immunological induction of histamine release 3,7,8. There have been even rarer hypersensitivity reactions to codeine, including generalized maculopapular eruptions, bullous eruptions, fixed drug eruptions, drug-induced hypersensitivity syndrome, or even toxic epidermal necrolysis 2,9-13. In this study, we confirmed anaphylaxis by OPT.…”
Section: Discussionmentioning
confidence: 99%